Criteria for the duration of anti-inflammatory therapy in children with bronchopulmonary dysplasia - Т. І. Stepanenko; I. M. Khrystosova; H. V. Rukavytsia (Zaporožskij Medicinskij Žurnal)
Objective. To develop criteria for determining the duration of anti-inflammatory therapy and indications for withdrawal of inhaled corticosteroids (ICS) in children with bronchopulmonary dysplasia (BPD).